Healthcare Simulations' Contributions to Improving Perinatal and Neonatal Practice: How Simulation Supports Interprofessional Collaboration, Organizational Learning, and Problem Solving. - Battista, Alexis (Journal of Perinatal & Neonatal Nursing)
This commentary examines evidence demonstrating how simulations have been used in the clinical setting to improve perinatal and neonatal clinical care, including simulations implemented to address select patient presentations, novel patient presentations, and those employed to test new clinical environments or renovated patient units. The underlying reasons these interventions support interprofessional collaboration, organizational learning, and problem solving are also discussed alongside common challenges associated with implementation.